2010
DOI: 10.1007/s12143-008-9021-x
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Foreign Direct Investment with Electronic Commerce in Less Developed Countries

Abstract: E-commerce, Foreign direct investment, Infrastructure, Information communication technologies, Development, Less-developed-countries,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…These sub-themes are addressed in the following subsections. 4 presents six studies that focus on the importance of IFDI in the IDP concept (Anwar and Nguyen 2010;Boudier-Bensebaa 2008;Chen et al 2020;Filippaios and Kottaridi 2013;Ly 2021;Pires et al 2010). The IDP depicts the process by which IFDI propels the augmented performance of domestic companies to escalate their O-specific advantages to engage in OFDI (Scott-Kennel and Enderwick 2005).…”
Section: Fdi Phenomena In the Idp Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…These sub-themes are addressed in the following subsections. 4 presents six studies that focus on the importance of IFDI in the IDP concept (Anwar and Nguyen 2010;Boudier-Bensebaa 2008;Chen et al 2020;Filippaios and Kottaridi 2013;Ly 2021;Pires et al 2010). The IDP depicts the process by which IFDI propels the augmented performance of domestic companies to escalate their O-specific advantages to engage in OFDI (Scott-Kennel and Enderwick 2005).…”
Section: Fdi Phenomena In the Idp Conceptmentioning
confidence: 99%
“…The positive role of IFDI depends on the characteristics of the locations (i.e., market size, improvement of macroeconomic conditions, and labour force quality) (Filippaios and Kottaridi 2013). Pires et al (2010) investigated the interaction between FDI in electronic commerce (e-commerce) and less developed countries. The study found that the factors that influence the attractiveness of IFDI in the e-commerce industry are the gap in technology infrastructure and conditions of legal, socioeconomic, and technical support (Pires et al 2010).…”
Section: The Importance Of Ifdi In Supporting the Development Of A Co...mentioning
confidence: 99%
See 1 more Smart Citation